Analysis of the Mechanism and Safety of Bisphosphonates in Patients with Lung Cancer and Bone Metastases. (13th December 2021) - Zhang, Gao; Gong, Hu; Xu, Hanqiao
Abstract : Objective . To explore the mechanism and safety of bisphosphonates in patients with lung cancer and bone metastases. Method . A total of 104 patients with lung cancer and bone metastases in our hospital were selected and randomly divided into two groups: control group (n = 54 ) and research group (n = 50 ). Chemotherapy was given to the control group, and the research group was treated with bisphosphonate drugs. The quality of life, HAMA, HAMD score, VAS score, treatment effect, serum calcium and KPS score, inflammatory factor levels, and immune function were compared between the two groups. Result . The quality of life in both groups was significantly increased (P < 0.05 ). The HAMA and HAMD scores of the research group decreased significantly than those of the control group after treatment (P < 0.05 ). The VAS scores of the two groups were significantly reduced (P < 0.05 ). The effective rates of treatment in the control group and the research group were 81.5% and 96.0%, respectively. Serum calcium was significantly decreased, and KPS score was significantly increased at weeks 1 and 6 after treatment, and the change was more obvious in the research group (P < 0.05 ). The levels of inflammatory factors in the two groups were significantly reduced, and the immune indicators were significantly increased. Conclusion . Bisphosphonates have good effect on patients with lung cancer and bone metastases, which can improve anxiety and depression, reduce pain score, improve serum calcium level and immune function, and reduce inflammatory response. Therefore, bisphosphonate drug therapy is worth widely used.